Comparison of two high‐resolution manometry software systems in evaluating esophageal motor function. Issue 12 (28th June 2016) - Rengarajan, A.; Drapekin, J.; Patel, A.; Gyawali, C. P.
Abstract: Background: High‐resolution manometry (HRM) utilizes software tools to diagnose esophageal motor disorders. Performance of these software metrics could be affected by averaging and by software characteristics of different manufacturers. Methods: High‐resolution manometry studies on 86 patients referred for antireflux surgery (61.6 ± 1.4 year, 70% F) and 20 healthy controls (27.9 ± 0.7 year, 45% F) were first subject to standard analysis (Medtronic, Duluth, GA, USA). Coordinates for each of 10 test swallows were exported and averaged to generate a composite swallow. The swallows and averaged composites were imported as ASCII file format into Manoview (Medtronic) and Medical Measurement Systems database reporter (MMS, Dover, NH, USA), and analyses repeated. Comparisons were made between standard and composite swallow interpretations. Key Results: Correlation between the two systems was high for mean distal contractile integral (DCI, r 2 ≥ 0.9) but lower for integrated relaxation pressure (IRP, r 2 = 0.7). Excluding achalasia, six patients with outflow obstruction (mean IRP 23.2 ± 2.1 with 10‐swallow average) were identified by both systems. An additional nine patients (10.5%) were identified as outflow obstruction (15 mmHg threshold) with MMS 10‐swallow and four with MMS composite swallow evaluation; only one was confirmed. Ineffective esophageal motility was diagnosed by 10‐swallow evaluation in 19 (22.1%) with Manoview, and 20 (23.3%) with MMS. On Manoview composite, 17 had DCI <450 mmHg/cm/s, and on MMS composite, 21, ( p ≥ 0.85 for each comparison) but these did not impact diagnostic conclusions. Conclusions & Inferences: Comparison of 10 swallow and composite swallows demonstrate variability in software metrics between manometry systems. Our data support use of manufacturer specific software metrics on 10‐swallow sequences. Abstract : Diagnostic value of high‐resolution manometry (HRM) software metrics could be affected by averaging and by software characteristics of different manufacturers. We exported and averaged coordinates of 10‐swallow manometry studies in patients referred for antireflux surgery and in controls; these single and composite swallows were imported back into two different HRM systems (Manoview, Medtronic; Medical Measurement Systems, MMS). Differences were noted between Manoview and MMS in IRP values generated, with overdiagnosis of outflow obstruction when Manoview IRP thresholds were applied to MMS composite swallows. Our data support using manufacturer specific thresholds for HRM software tools.